The Implementation of Classroom Management at Internship Program by Students of English Education Department Universitas Muhammadiyah Yogyakarta - Suci Anggorowati (PBI 15 UMY 057, 2015)
*57 Classroom management is important for teaching and learning process. Classroom management becomes a method to make sure that the activities and lesson in the classroom run well. This research focuses on the implementation of classroom management at internship program by students of English Education Department Universitas Muhammadiyah Yogyakarta and the obstacles that students faced in implementing classroom management. There were two research questions presented in this research: (1) how is the implementation of classroom management in internship program? (2) what are the obstacles faced by students of the English Education department in implementing classroom management?. The purposes of this research were to explore the implementation of classroom management in internship program and to explore the obstacles of students English Education Department in implementing classroom management. The researcher applied qualitative research design. Interview was used to collect the data. The research was conducted in Universitas Muhammadiyah Yogyakarta. The participants were students of English Education Department of Universitas Muhammadiyah Yogyakarta. The participants of this research were six students from batch 2011 who have taken classroom management subject. The result of this research showed that the students of English Education Department implemented classroom management. In the pre teaching, students applied greeting and warming up. During teaching, the students used group discussion and seat rolling in implementing classroom management. In addition, conclusion, summary and feedback were given by students in the post teaching.The problems faced by students of English Education Department of Universitas Muhammadiyah Yogyakarta were noise, disobedience, gadget playing and bullying.